Collapse episodes and remediation of subsidiary dam under construction of cut-off walls. Issue 2 (24th September 2018) - Zheng, Lingwei; Xie, Xinyu
Abstract : The main problems faced with earth dams relate to leakage, landslides and cracking, which are in turn related to seepage under and through dams. The construction of the Huangbizhuang reservoir began in 1958, and impounding started in 1960. The main purpose of the Huangbizhuang reservoir is flood control, while secondary uses are irrigation, fish farming, electricity generation and water supply. Many problems have occurred for more than 40 years of its operation. The construction of a seepage cut-off wall for the subsidiary dam began in March 1999. Seven dam collapses occurred during the construction of the cut-off walls. In this research study, the geological conditions of the site are considered, especially during the construction of the joint section of the cut-off wall (∼120 m long) where most of the collapses occurred. The methods for remediating the subsidiary dam of this reservoir are analysed and compared. Details of the collapses are described, and causes and improvement projects are proposed. Finally, suggestions regarding the construction of cut-off walls under such complex conditions are presented.